PENGARUH KINERJA DAN KOMITMEN TERHADAP BUDAYA ORGANISASI PT. SUMBER LAUTAN REZEKI - Enjellina Enjellina; Syawaluddin Syawaluddin; Aidil Putra (JURNAL BISNIS KOLEGA, 2020)
Abstract.This research was conducted at PT. Sumber Lautan Rezeki. The purpose of this study is to investigate and analyze the effect of Performance and Commitment on Organizational Culture. The population and sample in this study are: employees of PT. Sumber Lautan Rezeki, amounting to 39 people. The sampling technique used is saturation. Data collection techniques are by distributing questionnaires, interviews and documentation studies. Data analysis uses multiple linear regression analysis. The conclusion in this study is that simultaneously Performance and Commitment has a positive and significant effect on Organizational Culture of PT. Sumber Lautan Rezeki. Partially, the positive and significant effect on the organizational culture of PT. Sumber Lautan Rezeki. Partially, Commitment has positive and significant effect on Organizational Culture of PT. Sumber Lautan Rezeki. The magnitude of the coefficient of determination can be seen from the value of Adjusted R Square of 0.304 meaning that performance and commitment can explain organizational culture by 30.4% and the remaining 69.6% is influenced by other variables outside of this study such as: discipline work, competence, compensation and so on.Â Â Keywords: Performance, Commitment, Organizational Culture